DIGITAL MARKETING COMMUNICATION SUSTAINABLE HOTEL PRACTICE OF ACCOR GROUP IN SOCIAL MEDIA - Susilo, Daniel; Santos, Maria Clara K. (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Digital content becomes a big technical part in marketing work; it uses internet and Instagram media to publish their work and convey their message to the audience with involving their campaign on the progress. As Sustainability Development becomes trend for corporate responsibility, its law nature allowed it to become a trend. Therefore, in order to be successful, Accor Group also takes part in sustainability development, an important corporate responsibility yet at the same time maintaining their business. As a result, what Author gets from the analysis is that how their company profile and what they practiced in digital content synchronized each other, means that they did their duty properly.